2014
DOI: 10.1139/gen-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of three male-sterile, female-fertile mutants and generation of a comprehensive map of all known male sterility genes in soybean

Abstract: In soybean, an environmentally stable male sterility system is vital for making hybrid seed production commercially viable. Eleven male-sterile, female-fertile mutants (ms1, ms2, ms3, ms4, ms5, ms6, ms7, ms8, ms9, msMOS, and msp) have been identified in soybean. Of these, eight (ms2, ms3, ms5, ms7, ms8, ms9, msMOS, and msp) have been mapped to soybean chromosomes. The objectives of this study were to (i) locate the ms1, ms4, and ms6 genes to soybean chromosomes; (ii) generate genetic linkage maps of the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Obviously, the distortion may be caused by gametic selection. This hypothesis is partly supported by the presence of male sterile genes on chromosomes 2 and 13 (Jin et al 1998;Yang et al 2014). Based on the above results, we doubt that there are female and male sterile genes, respectively, in chromosomes 6 and 19.…”
Section: Discussionmentioning
confidence: 74%
“…Obviously, the distortion may be caused by gametic selection. This hypothesis is partly supported by the presence of male sterile genes on chromosomes 2 and 13 (Jin et al 1998;Yang et al 2014). Based on the above results, we doubt that there are female and male sterile genes, respectively, in chromosomes 6 and 19.…”
Section: Discussionmentioning
confidence: 74%
“…In soybean, 11 nuclear maleā€sterile mutants ( ms1 , ms2 , ms3 , ms4 , ms5 , ms6 , ms7 , ms8 , ms9 , msMOS and msp ) have been identified and studied (Yang et al., ). These mutants have been used mostly in population development and recurrent selection but not in hybrid seed production.…”
Section: Introductionmentioning
confidence: 99%
“…were close to ms1, ms3 ms4 and ms6, respectively (Cervantes- Martinez et al, 2009;Yang et al, 2014). In addition to this, the fe- Weigand, Perez, Palmer, & Sandhu, 2010;Ott et al, 2013;Yang et al, 2014), and ms6 gene showed linkage with the flower colour locus w1 (Palmer, Holland, & Lewers, 1998;Skorupska & Palmer, 1989). The MFMF gene from male-sterile and female-sterile soybean mutant was mapped to LG "D1a", close to the marker, Satt531 with 9.4 cM distance from the gene (Baumbach et al, 2012).…”
Section: Nms-related Genes In Soybeanmentioning
confidence: 73%
“…The ms1 and ms6 genes were located on LG ā€œFā€, and ms3 and ms4 genes were located on LG ā€œD1bā€. Molecular analyses revealed that the markers Satt516, Satt157, Satt542 BARCSOYSSR_02_1539 and AW186493 were close to ms1 , ms3 ms4 and ms6 , respectively (Cervantesā€Martinez et al, ; Yang et al, ). In addition to this, the femaleā€partial sterileā€1 ( Fsp1 ) and the Midwest Oilseed maleā€sterile ( msMOS ) mutants observed to locate on LG ā€œD1bā€ and Fsp1 , whilst the location of msMOS and ms3 was noticed in close proximity of marker Satt157 (Cervantesā€Martinez et al, ).…”
Section: Genetic Mechanism Of Male Sterility In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation